Pengaruh Komposisi Campuran Bahan Media Tanam dan Konsentrasi IBA terhadap Pertumbuhan Bibit Wani Ngumpen Bali (Mangifera caesia Jack) - I KADEK DWI MAHARDIKA; I NYOMAN RAI; I WAYAN WIRATMAJA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2013)
ABSTRACT The Influence of Composition Mixed Media Materials Plant and IBA Concentration on Growth of Seedlings Ngumpen Wani Bali (Mangifera caesia Jack) The experiment was conducted at plastic house at the Experimental Farm of the Faculty of Agriculture Udayana University Pegok, from January to May 2012. The objective of research was to determine the best concentration of growing media and plant growth regulators IBA to growth of seedlings wani Ngumpen Bali. The study used a randomized block design (RBD) with two factors. The first factor was growing media compositions comprising three types of media: soil + mixture of sand + organic matter (v: v: v = 3:2:1), soil + mixture of sand + organic matter (v: v: v = 3:1:2) and soil + mixture of sand + organic matter (v: v: v = 2:3:1). The second factor was four level of IBA i.e : 0 ppm, 50 ppm, 100 ppm, and 200 ppm. The results showed that treatment of growing media was not significant effect on plant height, number of leaves, stem segments, flushing cycle, stem diameter, leaf area and leaf NPK content of nutrients. While the concentration of IBA treatment was highly significant for plant height. Interactions between growing media and IBA concentrations was significantly on the nutrient content of N leaves only. The highest plant height was obtained at the 100 ppm IBA concentration (52.13 cm), while the lowest was obtained at control (36.74 cm). Keywords: Growing Media, IBA, Seeds, and Wani Ngumpen Bali